Meningkatkan Keterampilan Mengajar Guru Dengan Manajemen Kelas - Yusuf, Zulfikar; Anisatu Thoyyibah (LPPM UMRI, 2022)
The purpose of this activity is to produce educators who have competence in managing classes. By forming a paradigm as an educator, Knowing the characteristics of the students, and being able to make good planning and organizing in class management, all through public speaking, class management, and other things related to teaching. The dedication uses the andragogy approach which will lead to a two-way thinking process that uses various techniques, with training, simulation, and presentation. This relates to the strengthening of human resources from the internal